2009
DOI: 10.1073/pnas.0813144106
|View full text |Cite
|
Sign up to set email alerts
|

CXCL14 is an autocrine growth factor for fibroblasts and acts as a multi-modal stimulator of prostate tumor growth

Abstract: This study explored the role of secreted fibroblast-derived factors in prostate cancer growth. Analyses of matched normal and tumor tissue revealed up-regulation of CXCL14 in cancer-associated fibroblasts of a majority of prostate cancer. Fibroblasts overexpressing CXCL14 promoted the growth of prostate cancer xenografts, and increased tumor angiogenesis and macrophage infiltration. Mechanistic studies demonstrated that autocrine CXCL14-stimulation of fibroblasts stimulate migration and ERKdependent proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
218
3
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(234 citation statements)
references
References 26 publications
11
218
3
2
Order By: Relevance
“…In addition, other groups showed that CM from CAFs has a growth-promoting effect on tumor cells due to factors secreted in the culture medium (14,15). Among these factors, IL-6, TGFbeta, COX-2, and CXCL14 have already been mentioned (16)(17)(18)(19)(20). Interestingly, we show that our results are in accordance with Erez et al in that the proinflammatory gene signature was up-regulated in our fibroblasts in vitro as well, except for SPP1, which showed down-regulation upon tumor cell confrontation (21).…”
Section: Discussionsupporting
confidence: 82%
“…In addition, other groups showed that CM from CAFs has a growth-promoting effect on tumor cells due to factors secreted in the culture medium (14,15). Among these factors, IL-6, TGFbeta, COX-2, and CXCL14 have already been mentioned (16)(17)(18)(19)(20). Interestingly, we show that our results are in accordance with Erez et al in that the proinflammatory gene signature was up-regulated in our fibroblasts in vitro as well, except for SPP1, which showed down-regulation upon tumor cell confrontation (21).…”
Section: Discussionsupporting
confidence: 82%
“…These observations were supported by in vivo data: in a mouse model of transplantable mammary carcinoma, CAF-secreted CCL2 recruited macrophages into mammary tumours and specific ablation of CCL2 reduced tumour metastasis [65]. Other CAF-derived chemokines were also reported to enhance macrophage recruitment to various tumours: Augsten et al reported that prostate CAFs up-regulate CXCL14 that functioned to promote macrophage migration into prostate cancer xenografts [66]. Inhibition of NF-κB signalling, driving expression of CXCL1 and CXCL2 in skin CAFs, resulted in decreased macrophage infiltration into transplanted skin tumours and reduced tumour growth, indicating a central role for CAFs in facilitating the trafficking of macrophages into tumours [39].…”
Section: Activation By Paracrine Signallingmentioning
confidence: 82%
“…In vitro co-culture of macrophages with tumor cells has been shown to result in accelerated tumor growth [49]. TAMs express several factors, such as EGF, MMP-9, TGF-β and CXCL-14, that stimulate tumor cell proliferation and survival [50,51]. However, it is unclear whether macrophage density in tumor stroma is directly linked to tumor demography.…”
Section: Discussionmentioning
confidence: 99%